A Financial Recovery Plan for Vietnam Electricity : With Implications for Vietnam’s Power Sector - Maweni, Joel; Bisbey, Jyoti (World Bank, Washington, DC, 2016)
This report sets forth details of a financial recovery plan designed to help Vietnam Electricity (EVN), and the Vietnamese power sector more generally, to address a series of complex and interconnected challenges over the next 3 to 10 years. These challenges are operational and institutional as well as financial, and will lead to fundamental changes over time in the way that EVN and the overall power sector operate.